Behavior analytic contributions to public health and telehealth. Issue 3 (26th July 2020) - LeBlanc, Linda A.; Lerman, Dorothea C.; Normand, Matthew P.
Abstract : The Journal of Applied Behavior Analysis is launching a special series on the topics of public health and telehealth. The special series begins with the articles in this issue and will continue for the next 2 to 3 issues with an open submission window until September 1, 2020. Behavior analysis has much to offer with respect to public health and much to gain from continued and expanded use of telehealth. This paper outlines the importance of these topics in the current crisis and in our ongoing evolution as a field. The historical literature in behavior analysis is reviewed for each topic along with suggestions for future research. The articles from the special series will be combined with historical contributions from JABA into a virtual issue. We encourage continued submissions on these topics even after the special series is completed as future papers will also be incorporated into the special issue.